1999
DOI: 10.1177/136346079900200203
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Sexuality Among Immigrant Iranians in Canada

Abstract: This article presents an analytical study of the changing concepts of sexuality and gender relations among Iranian immigrants in Canada. I explore the ways in which spatial displacement transformed gender relations and sexuality. The impact of migration on gender is mediated through both class and gender relations. Migration effects profound changes in the compact between men and women. One fundamental change in gender and sexuality is the emphasis on individuality, which even among upper-middle-class families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 12 publications
0
19
0
2
Order By: Relevance
“…A good girl is expected to conceal her sexual desire from others, and even from herself, and not to speak of or fantasize about it. Shahidian (1999) described that once married, however, women are expected to be seductive and sexy, offering sex to their husbands to fulfill their marital duty (vazayef-e zanashooii). Sexual and gender norms for men carry similar contradictions.…”
Section: Introductionmentioning
confidence: 98%
“…A good girl is expected to conceal her sexual desire from others, and even from herself, and not to speak of or fantasize about it. Shahidian (1999) described that once married, however, women are expected to be seductive and sexy, offering sex to their husbands to fulfill their marital duty (vazayef-e zanashooii). Sexual and gender norms for men carry similar contradictions.…”
Section: Introductionmentioning
confidence: 98%
“…Other studies have shown that Muslim immigrants find themselves confronting traditionally held views, changing their outlook on some issues, becoming more detached from such collective beliefs -that relate to both culture and religion, and so more individualistic (Ahmadi, 2003a(Ahmadi, , 2003bFarahani, 2007;Shahidian, 1999) with a weakened sense of one's cultural heritage (Berry, 2011). However, as others have found (e.g., Hopkins, 2011; negotiating identity is often very complex, with different strategies used in different contexts, and that there is often a struggle between the need to belong as well acting assertively in developing a unique identity.…”
Section: Introductionmentioning
confidence: 99%
“…Z drugiej -tradycyjne wzorce kulturowe mogą być utrwalane przez rodzinę, grupę religijną czy społeczeństwo przyjmujące, mające określone oczekiwania względem kobiet pochodzących z tradycyjnej kultury (Espiritu 2003). Bez wątpienia migracja do innego kraju jest procesem, który ma potencjał wpływu na różne sfery życia jednostki, w tym na jej religijność (Connor 2008) i percepcję zjawisk społecznych, takich jak na przykład role związane z płcią kulturową (Shahidian 1999;Khalid 2011). Oznacza konfrontację z nowym językiem, kulturą religijną i obyczajami, które czasem istotnie różnią się od tych w kraju pochodzenia.…”
Section: Wstępunclassified
“…Zmodyfi kowane postawy częściowo oparte są na znaczeniach zaczerpniętych z kultury kraju przyjmującego, a częściowo kraju wysyłającego, co potwierdza wnioski Shahidian (por. Shahidian 1999). Respondentki nie łączyły religii z zagadnieniem społecznych ról kobiet i mężczyzn.…”
Section: Zakończenieunclassified